2015
DOI: 10.1002/tox.22222
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxidative phosphorylation signaling pathway on silkworm midgut following exposure to phoxim

Abstract: Organophosphate pesticides are applied widely in the world for agricultural purposes, and their exposures often resulted in non-cocooning of Bombyx mori in China. Silkworm midgut is the major organ for digestion and nutrient absorption, importantly it is also a barrier against foreign substances and chemical pesticides. The purpose of this study was to determine the mechanism of oxidative injury in silkworm midgut with phoxim induction. The results showed that the transcription level of oxidative phosphorylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Oxidative phosphorylation is a vital part of metabolism, it also produces reactive oxygen species such as superoxide and hydrogen peroxide, which leads to propagation of free radicals, damages cells and contributes to disease, and possibly ageing. The previous study showed that low temperature, UVB radiation and phoxim-induced increase in oxidative phosphorylation gene [ 39 41 ]. In the present study, 34DEPs were mapped to the oxidative phosphorylation pathway (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative phosphorylation is a vital part of metabolism, it also produces reactive oxygen species such as superoxide and hydrogen peroxide, which leads to propagation of free radicals, damages cells and contributes to disease, and possibly ageing. The previous study showed that low temperature, UVB radiation and phoxim-induced increase in oxidative phosphorylation gene [ 39 41 ]. In the present study, 34DEPs were mapped to the oxidative phosphorylation pathway (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…13 Previous studies reported that sublethal phoxim could also affect the nutrient metabolism in the midgut of B. mori, however, genes involved in energy metabolism were mostly upregulated at 24 h after phoxim exposure. 4,36 Taken together, the sublethal doses of pesticides could cause drastic changes in a variety of physiological processes in insects, and the different changes may be due to multiple factors, such as pesticide mode of action and dosage, treatment method and duration, insect species, developmental stage, and tissue type.…”
Section: Discussionmentioning
confidence: 99%
“…The midgut represents the primary targeted organs and the main site of digestion and absorption of materials in silkworm B. mori larvae (Franzetti et al, 2015). Several studies indicated the protective function of midgut against foreign and toxic compounds, through the release of enzymes (Zhang et al, 2014;Li et al, 2017;Wang et al, 2015). However, the digestion of toxic substances that may interfere with the composition of their diet unintentionally, such as the pesticide organophosphorus (OP), induced a serious adverse effect on midgut tissues (Shahare and Yashpal, 2013), including karyopyknosis and disappearance of the basal lamina, cell apoptosis (Zhang et al, 2014).…”
Section: The Histopathological Evaluation Of Midgut Samplesmentioning
confidence: 99%